High‐temperature thin‐film barriers for foldable AMOLED displays. Issue 4 (19th April 2018) - Akkerman, Hylke B.; Pendyala, Raghu K.; Panditha, Pradeep; Salem, Ahmed; Shen, Jie; van de Weijer, Peter; Bouten, Piet C.P.; de Winter, Suzanne H.P.M.; van Diesen‐Tempelaars, Karin; de Haas, Gerard; Steudel, Soeren; Huang, Ching‐Yu; et al.
Abstract: We present a thin‐film dual‐layer bottom barrier on polyimide that is compatible with 350°C backplane processing for organic light‐emitting diode displays and that can facilitate foldable active‐matrix organic light‐emitting diode devices with a bending radius of <2 mm. We demonstrate organic light‐emitting diodes that survive bending over 0.5 mm radius for 10.000× based on the high‐temperature bottom barrier. Furthermore, we show compatibility of the bottom barrier with the backplane process by fabricating active‐matrix organic light‐emitting diode displays on GEN1‐sized substrates. Abstract : We present a thin‐film dual‐layer bottom barrier on PI that is compatible with 350°C backplane processing for OLED displays and that can facilitate foldable AMOLED devices with a bending radius of <2 mm. We demonstrate OLEDs that survive bending over 0.5 mm radius for 10.000× based on the high‐temperature bottom barrier.